Artificial Upwelling in Singular and Recurring Mode: Consequences for Net Community Production and Metabolic Balance - Ortiz, Joaquin; Arístegui, Javier; Taucher, Jan; Riebesell, Ulf (Frontiers in Marine Science, 2022)
Artificial upwelling of nutrient-rich waters and the corresponding boost in primary productivity harbor the potential to enhance marine fishery yields and strengthen the biological pump for sequestration of atmospheric CO2. There is increasing urgency to understand this technology as a “ocean-based solution” for counteracting two major challenges of the 21st century—climate change and overfishing. Yet, little is known about the actual efficacy and/or possible side effects of artificial upwelling. We conducted a large-scale off-shore mesocosm study (∼44 m3) in the oligotrophic waters of the Canary Islands to identify the community-level effects of artificial upwelling on a natural oligotrophic plankton community. Four upwelling intensities were simulated (approx. 1.5/3/5.7/10 μmol L–1 of nitrate plus phosphate and silicate) via two different upwelling modes (a singular deep-water pulse vs. recurring supply every 4 days) for 37 days. Here we present results on the response of net community production (NCP), metabolic balance and phytoplankton community composition (<250 μm). Higher upwelling intensities yielded higher cumulative NCP. Following upwelling onset, the phytoplankton community became dominated by diatoms in all treatments, but other taxa such as Coccolithophores increased later in the experiment. The magnitude of effects on the metabolic balance scaled with the amount of added deep water, leading to (i) a balanced to net-heterotrophic system in the singular and (ii) a net-autotrophic system in the recurring upwelling treatments. Accordingly, the mode in which nutrients are supplied to an oligotrophic system plays a crucial role in the ecosystem response, with recurring upwelling leading to higher long-term positive NCP than singular upwelling. These results highlight the importance of empirically measured local responses to upwelling such as community structure and metabolism, with major implications for the potential employment of artificial upwelling as an ocean-based solution to generate (primary) production.